Mapping of Brain Activity in the Analgesia Induced by Phα1β and Morphine - Diniz, Danuza Montijo; Malamut, Carlos; Araújo, Marina Rios; Ferreira, Andrea Vidal; Silva, Juliana Figueira; Cordeiro, Marta do Nascimento; Borges, Marcia Helena; Romano Silva, Marco Aurélio; Gomez, Marcus Vinicius; Castro Junior, Célio Jose (Frontiers in Molecular Biosciences, 2022)
Preclinical evidence suggests the potential of Phα1β, a toxin obtained from the venom of spider Phoneutria nigriventer, as a new analgesic drug. In addition, molecular brain imaging techniques have afforded exciting opportunities to examine brain processes in clinical pain conditions. This paper aims to study the brain regions involved in the analgesic effects of Phα1β compared with morphine in a model of acute pain induced by formalin in Sprague Dawley rats. We used 18F-fluorodeoxyglucose as a metabolic radiotracer to perform brain imaging of rats pretreated with Phα1β or morphine in a model of acute inflammatory pain caused by intraplantar injection of formalin. The rats' hind paw's formalin stimulation resulted in a brain metabolic increase at the bilateral motor cortex, visual cortex, somatosensory cortex, thalamus, and cingulate cortex. In rats treated with Phα1β, selective inhibition of unilateral motor cortex and cingulate cortex was observed. In addition, morphine treatment leads to small and selective inhibition at the bilateral amygdala striatum and accumbens. Thus, our results indicate that the analgesic effect of Phα1β and morphine possesses a differential profile of central processing in the pain state.